Possible role of waxes in powdery mildew resistance in Zizhyphus - N.D. JAMBHALE, T. PRADEEP* and (Indian Phytopathology, 2002)
Total epicuticular wax content in immature fruits of ten ber genotypes and mature leaves of 3 genotypes varying in their ploidy levels and reaction to powdery mildew (PM) caused by Oidium erysiphoides f. zizhyphi was investigated. Quantitative variations were observed, the wax content being high in diploid resistant genotypes except Gull than the tetraploid susceptible ones. Similarly Seedless an octaploid immune genotype had higher leaf waxes than Darakhi-I (resistant) and Kadaka (susceptible). However its fruits had lower wax content as that of Illaichi, another octaploid susceptible genotype. Thus the pattern of quantitative variation observed for wax content between the resistant and susceptible genotypes of ber suggest that wax may not be the only factor imparting resistance to powdery mildew disease.